Resumos Expandidos : Campus Maruípe - da Silva Martins, Guilherme Vinícius; Brener Nascimento Carlini, Marcelo; Freitas, Marcus Ferreira de; Barbosa, Wagner Miranda; Hocayen de Paula, Adriana (Revista Guará, 2023)
Resumos Expandidos Campus Maruípe